பேராசிரியர் ந. சுப்பு ரெட்டியாரின் ‘வள்ளுவரின் வாழ்வியல் சிந்தனைகள்’ தெளிவுறுத்தும் அறமும், அறவியல் வாழ்வும் / Virtue and Moral Life in Professor N. Subbu Reddiar’s ‘Valluvarin Vaazhviyal Sinthanaigal’ - முனைவர் ப. சு. மூவேந்தன் / Dr. P. S. Mooventhan (International Journal of Tamil Language and Literary Studies, 2022)
Virtue is the chief moral code of common life in Tamil society. Virtues arose with the primary aim of emphasizing virtue. “Tirukkural” is the chief among the didactic books. “Tirukkural” has created many ideas with very few words like the English saying “Brevity is the Soul of Wit. Professor Subbu Reddiar studied the concept of “Tirukkural” in his commentary, speech and writing. Such interpretations were in texts, paraphrases, translations, textual interpretations, and textual refutations. Prof. N. Subbu Reddiar has authored many books related to “Tirukkural” and didactic books. One of them is ‘Vaḷḷuvariṉ Vāḻviyal Cintaṉaikaḷ’. This is a testament to Professor's introspective vision. In this book, he has explained the meaning of virtue and how it has been followed in Tamil tradition. The virtues created by “Tirukkural” and its functions, the need for virtue in life, the virtues and the ability of Tirukkural's thoughts are seen in his works. In this way, this book also serves as an explanatory manual for “Tirukkural”. In this, he has revealed the meaning of virtue, material, and pleasure in terms of virtue in virtue, virtue in material, and virtue in pleasure. Moreover, he has tried to realize through this book that virtue is proof of the excellence of the Tamil language. He has also shown that he has been continuously associated with “Tirukkural” since his youth with his life events. In this article, Prof. N. Subbu Reddiar's ability to analyze “Tirukkural” with Tamil life and the compatibility of “Tirukkural” with his life has been evident. Hence, the objective of this research paper is to examine the importance of virtue, meaning, and pleasure, and the relevance of virtue with evidence through the book ‘Valluvarin Vaazhviyal Sinthanaigal’.